The Importance of Religion in Adolescents’ Lives - Schneider, Barbara; Rice, Holly; Hoogstra, Lisa (Catholic Education: A Journal of Inquiry and Practice, 2004)
This study examines the importance and relative impact of religious behaviors in the development of adolescents. The links among adolescents’ positive emotional and behavioral outcomes, religious practices in the home, and extracurricular activities at school are explored.